INCIDENCE OF ISOPARORCHlS HYPSELOBAGRI (BILLET, 1898) (fREMATODA, HEMIURIDAE) AMONG THE CATFISHES OF BHAVANISAGAR RESERVOIR - Devaraj, M; Ranganathan, V (Indian Journal of Fisheries, 2011)
Southwell (1913) described lsoparorchis hypselobagri. found inside the cavity of the air-bladdel of a freshwater catfish, WaJlago attu, caught from a tank at Bankipur, Bengal. He observed cent per cent infection in the adult W, attu examined. According to him, the worms collected by Capt. Parker in 1910 from the flesh of the mabseer, Barhus tor, were immature I. hypselobagri. Achan (1956) recorded 65 per cent infection among this fish in the Bhavanisagar reservoir with a maximum of fOfty worms in a single host. The incidence of this worm in the air-bladder of W. atfu, in the viscera and body musculature of Ca/lichrous bimaculatus and the destruction of the ovary in Mystus oar and some aspects of host-parasite relationship based on observations made during 1964-65 are described in this communication.